IMPLEMENTATION OF THE THERAPEUTIC COMMUNITY METHOD FOR DRUG ABUSE IN CLASS IIB NARCOTICS PRISON PURWOKERTO - Firsty Aulia Oryza Sativa; Odi Jarodi (Journal of Management Small and Medium Enterprises (SME's))
The implementation of the social rehabilitation program using the Therapeutic Community (TC) method at the Narcotics Prison of Purwokerto has shown significant progress. The program consists of planning, execution, and evaluation stages. Initially, residents undergo a screening process, followed by orientation and the primary phase, where they engage in structured activities aimed at behavioral change. The re-entry phase, although hindered by the mixing of residents with other inmates, provides opportunities for adaptation through vocational training and family counseling. While the aftercare stage is not conducted within the prison, strategies are developed to prepare former residents for independent living. Challenges such as limited human resources and inadequate facilities are identified and evaluated for improvement. Recommendations include enhancing collaboration with relevant agencies and providing specialized training for staff to optimize the rehabilitation program's effectiveness.